1991
DOI: 10.1002/1097-0142(19910801)68:3<502::aid-cncr2820680310>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservation therapy. Severe breast fibrosis after radiation therapy in patients with collagen vascular disease

Abstract: Two patients with collagen vascular disease (rheumatoid arthritis and scleroderma) had extremely poor cosmetic results after breast radiation therapy (RT). The patient with rheumatoid arthritis received 5251 cGy at 210 cGy per day, followed by a 1600 cGy iridium-192 implant boost. Between 8 and 11 months post-RT she had severe breast fibrosis, retraction, and pain that required a mastectomy for relief. The patient with scleroderma received 5040 cGy at 180 cGy per day without a boost. Between 1 and 4 months pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(40 citation statements)
references
References 15 publications
1
35
1
2
Order By: Relevance
“…Early publications were largely case reports of CVD patients with increased toxicity from RT. [1][2][3][4][5][6][7][8] However, 2 separate matched control studies failed to observe any increased risk of acute or late complications in patients with CVD versus patients without CVD. 9,10 Other publications suggested that patients with nonrheumatoid arthritis CVD, 11,12 or patients with specific subtypes of CVD, may be at increased toxicity risk.…”
mentioning
confidence: 99%
“…Early publications were largely case reports of CVD patients with increased toxicity from RT. [1][2][3][4][5][6][7][8] However, 2 separate matched control studies failed to observe any increased risk of acute or late complications in patients with CVD versus patients without CVD. 9,10 Other publications suggested that patients with nonrheumatoid arthritis CVD, 11,12 or patients with specific subtypes of CVD, may be at increased toxicity risk.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Scleroderma is a vascular disease marked by fibrosis, similar to what is often observed in late radiation injury. In normal individuals (ie no autoimmune disease), radiation therapy has been reported to be the initiating event for development of localized scleroderma usually within the radiation port but also at sites distal to the radiation field.…”
Section: Treatment Of Scleroderma With Radiationmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] In patients with scleroderma, numerous papers have reported severe radiation-induced toxicity. [30][31][32][33][34] When using high-dose (40-70 cGy) localized radiation to treat cancer in patients with scleroderma, radiation-related injury may extended beyond the radiation field and causes death in approximately a third of patients and/or severe fibrosis overlapping the radiation field in the survivors. Patients with scleroderma undergoing breast irradiation have a significant increase in radiation-related complications including arm edema, chest wall necrosis, brachial plexopathy, pneumonitis, severe cutaneous fibrosis with retractions, and fistulae.…”
Section: Treatment Of Scleroderma With Radiationmentioning
confidence: 99%
“…The review of the literature documents no case of stenosis of the esophagus or trachea after radiotherapy of Castleman disease. However, autoimmune disorders such as systemic lupus erythematosus and scleroderma have been reported to be associated with an increased incidence of long term radiation sequelae involving the skin and soft tissues [24,25]. Late complications reported include severe fibrosis and/or necrosis of the skin, breast, bowel, and pelvis.…”
Section: Discussionmentioning
confidence: 99%